A comparative study on the learning styles of second year education (Living Skills) students and the teaching styles of their lecturers - Ibrahim, Noor Mala; Ramli, Nor Hidayah (2010)
Learners’ learning styles are the most important factors in determining how well they learn second language. The success however is very much dependent not only on learner’s learning style but also teacher’s teaching style. However there has always been a mismatch between learners’ learning styles and teacher’s teaching style and therefore language learners do not learn effectively. This research was set out to investigate on the issue and to reveal the learning styles of University Technology Malaysia second year students from Faculty of Education who are majoring in Living Skills as well as the social and surrounding factors that influence their language learning styles and preferences. This study also investigated on the students’ view on their lecturer’s teaching style and consequently the problems that they encountered during the implementation of Advanced English for Academic Communication (UHB 2422) class due to the mismatch of their learning styles and lecturer’s teaching style. A number of 50 UTM students who are majoring in Education (Living Skills) became the respondents and the research instrument used was questionnaire. This research found out that the most preferred learning styles of the students is kinesthetic style while the major factor that influence their learning style is their course and major of study. Most of their lecturers are perceived as having visual teaching style. Out of 50 students, only 6 students have their learning styles matched with their lecturers’ teaching styles. The main problem encountered by the students is they felt drowsy during the class. This study recommended teacher or language instructor to vary their teaching style and match their teaching styles with their learners’ learning styles in order to ensure an effective teaching and learning.